Asbab Al-Nuzul Mengungkap Latar Belakang Turunnya Ayat-Ayat Al-Quran. - Sintia Fa'iz Rahmadina; Setyo Anas Hendro; Muhammad Noval Indra Jaya; Hakmi Hidayat (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2025)
Asbab an-Nuzull is a science that discusses the reasons for the revelation of the verses of the Quran, which certainly plays an important role in understanding the historical context and the laws contained therein. This study aims to explain the concept of Asbab an-Nuzull, the division of its types, as well as its urgency and benefits in the science of tafsir. Through literature review from various scholars, it is found that Asbab an-Nuzul is divided into two main forms, namely event-based and question-based. In addition, an understanding of Asbab an-Nuzul can help avoid errors in the interpretation of verses and provide a deeper insight into the background of the revelation of Quranic verses. Therefore, knowledge of Asbab an-Nuzul is essential for mufassirs when interpreting the Quran more accurately and contextually.